A GOVERNMENT ROLE THROUGH ICT FOR ECONOMIC GROWTH - Eddy Irsan Siregar; Wiwiek Prihandini; Muhammad Gunawan Setyadi; Muhammad Ihyakulumudin (Universitas Lancang Kuning, 2022)
- The economic growth processes and their acceleration have become essential factors in solving social and economic problems. Innovation-driven Information and Communication Technology (ICT) is believed to be the driver of economic growth. However, ICT raises the digital divide problem, which weakens the influence of ICT on economic growth. This study aims to develop a model that can explain the role of government as a factor that strengthens the influence of ICT on economic growth. The model is formulated using data from 114 countries listed in the Network Readiness Index (NRI) 2019. The study results prove that the digital divide is a factor that weakens the influence of ICT on economic growth and the role of government as a factor that strengthens the influence of ICT development on economic growth. This study recommends that innovations for ICT development provide options for countries that find it challenging to invest in ICT development, especially for 4.0 or 5.0 technological innovations. Nevertheless, human resource development is used to realize innovations in ICT development.